Experimental tests for seismic assessment and strengthening of adobe structures - Oliveira, C. (2012)
Adobe structures present very appealing characteristics regarding a more sustainable practice with the preservation of our natural resources. However, when subjected to cyclic horizontal actions, such as earthquakes, they can present a deficient behaviour. With the purpose of evaluating the seismic vulnerability of adobe structures, a series of tests were conducted on a full-scale adobe wall considering constant dead and live loads combined with cyclic horizontal actions with rising amplitude. A structural strengthening solution was tested on the repaired wall after its assessment test. The adopted repair solution, based on cracks injection, combined with the strengthening solution, proved to be very efficient in improving the performance of the adobe wall. With the study conducted, it was possible to contribute to the characterization of adobe structural walls in terms of deformation capacity and failure modes, establishing the basis for the calibration of numerical models for adobe structures.